Análisis y verificación del modelo gaussiano de dispersión: métodos teóricos y experimentales (2019)
The dispersion of pollutants is a phenomenon of necessary understanding to size and forecast the concentration and mixture of gases generated by mobile and fixed sources in the lower atmosphere; Howevwe, this mobilization of chemical substances in the air by the action of gradients of pressure, temperature and concentration is not completely predictable or reproducible in the laboratory, which is why contaminant dispersion models and test benches have become a recurrent alternative in environmental studies. For this reason, it is necessary to confront the theoretical and experimental modeling using the Chamber of Interaction and Simulation of Atmospheric Pollutants -CISCA UC- in order to identify correlations and their applicability for certain studies. In order to carry out this comparison, multiple tests with carbon dioxide were made in the chamber, simulations in the Screen View software and in the Excel spreadsheet, developing the mathematics of the Gaussian model. It was evidenced that the Gaussian bell is representative for disérsion at a maximum height of 1.5 km, which in most cases equals the maxing height. In conclusion, it was possible to verify that the test bench is very useful to represent three-dimensional dispersion under controlled conditions and that the reality of the dispersion is in accordance with the Gaussian tendency.